Infection-Related Hospitalization in Heart Failure With Reduced Ejection Fraction: A Prospective Observational Cohort Study. (May 2020) - Drozd, Michael; Garland, Ellis; Walker, Andrew M.N.; Slater, Thomas A.; Koshy, Aaron; Straw, Sam; Gierula, John; Paton, Maria; Lowry, Judith; Sapsford, Robert; Witte, Klaus K.; Kearney, Mark T.; et al.
Abstract : Background: Hospitalization is a common adverse event in people with heart failure and reduced ejection fraction, yet is often not primarily due to decompensated heart failure (HF). We investigated the long-term prognosis following infection-related hospitalization. Methods: We conducted a prospective observational cohort study of 711 people with heart failure and reduced ejection fraction recruited from 4 specialist HF clinics in the United Kingdom. All hospitalization episodes (n=1568) were recorded and categorized as primarily due to decompensated HF, other cardiovascular disease, infection-related, or other noncardiovascular disease. Survival was determined after the first hospitalization. Results: During 2900 patient-years of follow-up, there were a total of 14 686 hospital days. At least one hospitalization occurred in 467 people (66%); 25% of first hospitalizations were primarily due to infection and these were not associated with typical signs including tachycardia and pyrexia. Compared with other categories of hospitalization, infection-related was associated with older age, lower serum albumin, higher blood neutrophil counts, and greater prevalence of chronic obstructive pulmonary disease at recruitment. Median survival after first infection-related hospitalization was 18.6 months, comparable to that after first decompensated HF hospitalization, even after age-sex adjustment. The burden of all-cause rehospitalization was comparable irrespective of the category of first hospitalization, but infection more commonly caused re-hospitalization after index infection hospitalization. Conclusions: Infection is a common driver of hospitalization in heart failure and reduced ejection fraction and often presents without classical signs. It is associated with high mortality rates, comparable to decompensated HF, and a major burden of rehospitalization caused by recurrent episodes of infection. Abstract : Supplemental Digital Content is available in the text.